Menelusuri Efisiensi Rantai Pasokan: Studi Kasus Helomart di Kabupaten Pesawaran - Wardana, M. Azka Kesuma; Kurniawan, Rudi; Prikurnia, Anas Khair (Journal of Economic and Business Retail, 2025)
This study explores the efficiency of supply chain management in a small-scale minimarket located in Pesawaran Regency, Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews with the minimarket owner and direct observation of daily operational activities. The study reveals three main themes influencing supply chain efficiency: procurement strategies based on real-time needs, limitations in digital inventory systems, and informal supplier relationships. The minimarket utilizes adaptive procurement without predictive planning, resulting in flexibility and reduced overstock risk, but also leads to increased logistical costs due to frequent restocking. Inventory control remains manual and non-digitalized, making it difficult to generate real-time stock data and performance insights. In addition, supplier relationships are built on informal agreements and personal trust, providing short-term efficiency but posing risks due to high dependency on a limited number of vendors. This study highlights the contextual nature of supply chain efficiency in small retail operations, emphasizing the need for basic digital adoption, data-based decision making, and supplier diversification. The findings are expected to offer practical insights for small-scale retailers and inform local policymakers in improving operational resilience and competitiveness in rural retail sectors.